Determining food safety of plasma-chemically activated water and bread based on it - Mykolenko, Svitlana; Миколенко, Світлана Юріївна; Pivovarov, Olexandr; Півоваров, Олександр Андрійович; Yefimov, Valentyn; Єфімов, Валентин Геннадійович; Sova, Nataliia; Сова, Наталія Анатоліївна; Tymchak, Dmytro; Тимчак, Дмитро Олександрович (ПП "ТЕХНОЛОГІЧНИЙ ЦЕНТР" Український державний університет залізничного транспорту, 2021)
Water treatment by contact non-equilibrium low-temperature plasma refers to innovative methods of processing food raw materials, which requires determining the level of safety of its use to meet the requirements of food safety for humans. The test animals were divided into four test groups with two different basic diets. The tested substances were drinking main water (control group) and plasma-chemically activated water (experimental group); wheat bread (control group) and wheat bread produced using plasma-chemically activated water (experimental group). It was found that there was no significant difference between the control and experimental groups of animals in body weight and its changes during 90 days of the introduction of the test substances into the diet. The amount of water and feed consumed was in direct proportion to the change in the weight of animals in the corresponding diets. The hematological and biochemical analysis of the blood of the test rats did not confirm the toxic or allergenic effect of the studied feeding factors on their organism. An increase in the number of erythrocytes in the blood and activation of the phagocytic activity of experimental groups of animals were confirmed. This confirms the positive effect of plasma-chemically activated water and wheat bread made with its use on metabolic processes in the body of animals. Macromorphological parameters of the body of animals and the results of histological studies of the stomach, liver, kidneys and femur as potential target organs demonstrated the absence of dystrophic-degenerative changes in these organs. A comprehensive study of the food safety of plasma-chemically activated water and wheat bread made with its use proves the possibility of using an innovative method of water treatment in food production. Обробка води контактною нерівноважною низькотемпературною плазмою води відноситься до інноваційних методів обробки харчової сировини, що потребує визначення рівня безпечності її застосування задля задоволення вимог нешкідливості харчових продуктів для людини. Піддослідні тварини було поділено на чотири тест-групи з двома різними базовими раціонами. Тестованими речовинами були питна магістральна вода (контрольна група) і плазмохімічно активована вода (дослідна група); пшеничний хліб (контрольна група) і пшеничний хліб, виготовлений з використанням плазмохімічно активованої води (дослідна група). Встановлено, що суттєвої різниці між контрольними і дослідними групами тварин за масою тіла та її зміною протягом 90 днів введення тестованих речовин до складу раціону харчування не відбувалось. Кількість спожитої води і корму була прямопропорційна зміні маси тварин відповідних раціонів. Гематологічний і біохімічний аналіз крові піддослідних щурів не засвідчив токсичної чи алергенної дії досліджених кормових чинників на їх організм. При цьому підтверджено підвищення кількості еритроцитів у крові та активацію фагоцитарної активності дослідних груп тварин. Це підтверджує позитивний вплив плазмохімічно активованої води і пшеничного хліба, виготовленого з її використанням, на метаболічні процеси в організмі тварин. Макроморфологічні параметри тіла тварин і результати гістологічних досліджень шлунку, печінки, нирок і стегнової кістки як потенційних органів-мішений продемострували відсутність дистрофічно-дегенеративних змін у вказаних органах. Комплексне дослідження харчової безпечності плазмохімічно активованої води і пшеничного хліба, виготовленого з її використанням, доводить можливість застосування такого інноваційного методу обробки води у харчовому виробництві
Визначення харчової безпечності плазмохімічно активованої води і хліба на її основі
Keywords: plasma-chemically activated water; плазмохімічно активована вода; food safety; харчова безпечність; wheat bread; пшеничний хліб; subchronic toxicity; субхронічна токсичність